An Interconnection between Earnings Quality and Earnings Management in the Business Environment - Emad Saleem EL Agha; Norfadzilah Rashid (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
This paper reviews the interconnection between earnings quality and earnings management in the business environment, through the use of flexibility in determining the practices and methods as well as accounting estimates, to change the income that affecting disclosure process when preparing the financial statements. Which will be based on many of the misinformation, through corporate management manipulation results of company profits and losses and financial position statement. These multiple reasons include capital market motivations to raise their share prices and attract potential shareholders. In addition, the motives of borrowing loans and funding. All this leads to the loss of the most important characteristics of the quality of representation is sincere of accounting information. Therefore, will negatively affect the quality of accounting profits. This is one of the most important information that concerns the shareholders. By consideration, the earnings quality and earnings management are two related challenging interwoven issues in financial reporting as earnings management is an aspect influencing earnings quality. In this paper, fundamental scientific processes such as analysis, synthesis, induction, and deduction have been utilized in order to achieve the objective of this paper. This paper concluded that earnings management has a negative impact on the quality of earnings if it distorts the information in a way that is less useful for forecasting future cash flows, which in turn result in unreliable financial reports leading to incorrect decision. Also, corporate earnings of high quality are those that have a high level of persistence, are more timely, more predictable, less volatile and have lower level of earnings management. And on the other side it is important to understand that lower earnings quality are not indicators of poor financial situation or the misapplication of accounting policies, judgments, and estimates.